Quality of life, clinical outcome, personality and coping in chronic hemodialysis patients. (1st January 2017) - D'Onofrio, Giuseppina; Simeoni, Mariadelina; Rizza, Paolo; Caroleo, Mariarita; Capria, Maria; Mazzitello, Giovanni; Sacco, Tiziana; Mazzuca, Elena; Panzino, Maria Teresa; Cerantonio, Annamaria; Segura-Garcia, Cristina; Andreucci, Michele; et al.
Abstract: Rational: Our aim was to investigate the quality of life (QoL) in 103 patients undergoing chronic hemodialysis (HD) in an integrated assessment of clinical, personological, and adaptation parameters, also in a non-urban context. Objectives: We collected data from all chronic HD patients attending four HD units. Clinical status was assessed by Kidney Disease Outcomes Quality Initiative (KDOQI) guidelines and by Age-adjusted Charlson Comorbidity Index (ACCI). Patients completed the following questionnaires: Kidney Disease Quality of Life Short Form (KDQOL-SF), Pittsburgh Sleep Quality Index (PSQI). Personality profile and coping style were assessed by Temperament and Character Inventory (TCI) revised and Coping Inventory for Stressful Situation (CISS). Data were analyzed by conventional descriptive statistics. Multiple forward stepwise linear regression analyses were performed. Main findings: Variables significantly associated with physical and mental components of KDQOL-SF were: intact parathyroid hormone (iPTH) ( p  = .004; p  = .0015), typology of cohabitant (family member or not) ( p  = .022; p  = .007), years of dialysis ( p  = .022; p  = .048). Variables associated with mental component of KDQOL-SF were: PSQI ( p  = .000), task-coping ( p  = .000), avoidance-coping ( p  = .003), work status ( p  = .021). Principle conclusions: Our results suggest the importance of an integrated and multidirectional management of patients chronically undergoing HD and living in a non-urban context.